Metabolic impact of endogenously produced estrogens by adipose tissue in females and males across the lifespan - Lee, Angel A.; Den Hartigh, Laura J. (Frontiers in Endocrinology, 2025)
The aged population, expected to double by 2050, makes up a large proportion of people living with metabolic disease. Obesity rates in the elderly are rapidly increasing, with estimates that nearly 40% of men and women over the age of 60 are classified as obese. White adipose tissue (WAT) is a highly metabolically active organ that undergoes significant changes during both obesity and aging, and metabolic dysfunction in WAT is a major cause for elevated diabetes risk. A marked difference in fat distribution is often reported between men and women. Many studies suggest that pre-menopausal women are protected from the accumulation of visceral adiposity due to gonadal estrogen, which exerts cardiometabolic benefits. Men with obesity harbor a disproportionately higher volume of intra-abdominal fat than premenopausal age-matched women with obesity, an effect that is negated by menopause as women begin to gain intra-abdominal fat. Post-menopausal women are at increased risk of developing diabetes, which can be mitigated by estrogen replacement therapy, suggesting an important role for sex steroids in diabetes risk. In addition to being highly responsive to gonadal estrogens, WAT has the capacity to convert androgens into estrogens, which may similarly impact WAT distribution and metabolism. Estrogens, comprised primarily of estrone (E1) and estradiol (E2) within WAT, are biosynthesized from circulating androgens androstenedione (A4) and testosterone (T) by aromatase (CYP19A1), which is highly expressed in human and mouse adipose tissue. In post-menopausal women, WAT becomes the predominant source of estrogen production, with age-associated increases in WAT aromatase expression that are mirrored by obesity. In contrast to ovarian estrogen production, in which E2 is the predominant estrogen type, E1 tends to be the predominant estrogen post-menopause. To date, little is known about WAT-derived estrogens and their impact on metabolic health, but emerging evidence suggests that increased E1 levels may contribute to metabolic dysfunction in aging. This review will introduce known sex differences in adipose metabolism associated with aging, obesity, and diabetes, and discuss the impact of WAT-derived sex hormones on local and systemic metabolism.